2016
DOI: 10.1021/acsami.5b11741
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Phosphonate-Functionalized Mesoporous Silica Nanoparticles

Abstract: In this work, we synthesized pristine mesoporous silica nanoparticles (MSN) and functionalized these with phosphonate groups (MSN-Phos). We report, for the first time, cell death in MCF-7 cells (human breast adenocarcinoma cell line) when exposed to the empty MSN and MSN-Phos nanoparticles. In comparison, the same nanoparticles were found to elicit few deleterious effects on normal human foreskin fibroblast cells (BJ cells). MCF-7 cells were found to exhibit a concentration-dependent uptake, whereas no detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…As shown in Table 2, the obtained IC 50 results show no significant cytotoxicity after 24 hours of treatment of blank MSN-NH 2 , MSN-Met, and MSN-FA on MCF-7 cells. It can be concluded that MSNs are biocompatible carriers and play no role in toxicity in MCF-7 cells 64,65. Overall, results attest to the potential of DTX/MSNs for DTX delivery by increasing the effectiveness of targeted delivery.…”
Section: Resultsmentioning
confidence: 62%
“…As shown in Table 2, the obtained IC 50 results show no significant cytotoxicity after 24 hours of treatment of blank MSN-NH 2 , MSN-Met, and MSN-FA on MCF-7 cells. It can be concluded that MSNs are biocompatible carriers and play no role in toxicity in MCF-7 cells 64,65. Overall, results attest to the potential of DTX/MSNs for DTX delivery by increasing the effectiveness of targeted delivery.…”
Section: Resultsmentioning
confidence: 62%
“…MSNs had several peaks at 450, 800, and 1056 cm −1 because of the siliceous mesostructured framework. As their surface was functionalized with phosphonate groups in MSNsP, we observed a new band at 953 cm −1 and a broad peak from 3000 to 3600 cm −1 , reflecting phosphonate groups [39]. Two new peaks at 1639 cm −1 , and an intensive peak centered at 3355 cm −1 were presented in MSNsPCOL, corresponding to shifted peaks at 1542 and 3629 cm −1 for COL. Additional coating resulted in several new peaks, with bands at 698 and 946 cm −1 attributed to chitosan, glycine, or folic acid.…”
Section: Functional Group Determinationmentioning
confidence: 73%
“…Besides cytotoxicity, previous study also found that silica coating significantly reduce DNA damage induced by ZnO nanorods [51]. Comparison between ZnO NPs and SiO 2 NPs also found that ZnO NPs are more toxic [52, 53, 54, 55]. …”
Section: Resultsmentioning
confidence: 98%